THE APPLICATION QUEUEING THEORY IN SINGKIL SERVICE CAR WASH - Bongkriwan, Melisa Irene; Tumewu, Ferdinand (Universitas Sam Ratulangi, 2015)
In the service industry, long queuing will for waiting to be served is a taboo. Since, customers will switch to other competitors and reduce revenues. This research is conducted to find out the effectiveness and efficiency in queuing system in order to achieve customer satisfaction in the Singkil Service Car Wash. This research used model B M/M/S formula to get the average incoming customer. In normal condition, there were 2 customers and 3 line services, in the quiet condition, 1 customer and 2 line services, in the crowded condition there were 3 customers and 4 line services. The Singkil Service Car Wash performance is under optimal condition since the number of customers who came is still low. It is advisable to the owner of the Singkil Service Car Wash to reduce the service line and to reassign the unproductive employees to other area so the worker productivity can be retained. This will result in a more efficient and effective employee’s management and better profit for the company. Keywords: queueing system, singkil service car wash